2020
DOI: 10.1155/2020/3819514
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Social Networks on Citizens’ Willingness to Participate in Social Governance: Evidence from China

Abstract: Social networks are social structure constituted by a set of social actors with embedded relationships, which has a significant impact on both perceptions and behaviors among individuals and groups. The influence of the social networks on citizens’ willingness to participate in social governance is manifested in two aspects: one is that social networks directly affects the citizens’ willingness to participate; the other is the social capital made up by social networks, social trust, and social norms affects th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…This finding was also supported by Jagannathan et al (2021) with results revealing that capability in terms of social network encourages community participation in community-related initiatives using the principles of community organization and this helps to produce desired outputs and improve the well-being of the participants through better and representative policies (Jagannathan et al, 2021). They are also in line with the study findings of Nan and Ouyang (2020) who reported that capability in terms of social networks has a significant role it plays in increasing citizens' ability and willingness to use engagement tools to engage in policy formulation through e-participation more so when the network ties are strong (Nan and Ouyang, 2020;Starke et al, 2020). This is further…”
Section: Discussion and Interpretation Of Study Findingssupporting
confidence: 73%
See 3 more Smart Citations
“…This finding was also supported by Jagannathan et al (2021) with results revealing that capability in terms of social network encourages community participation in community-related initiatives using the principles of community organization and this helps to produce desired outputs and improve the well-being of the participants through better and representative policies (Jagannathan et al, 2021). They are also in line with the study findings of Nan and Ouyang (2020) who reported that capability in terms of social networks has a significant role it plays in increasing citizens' ability and willingness to use engagement tools to engage in policy formulation through e-participation more so when the network ties are strong (Nan and Ouyang, 2020;Starke et al, 2020). This is further…”
Section: Discussion and Interpretation Of Study Findingssupporting
confidence: 73%
“…Besides that, study findings of Jagannathan et al (2021) reported that social network encourages community participation in community-related initiatives and citizen engagement in policy formulation. Also, the study findings of Nan and Ouyang (2020) reported that social networks play a significant role in increasing citizens' ability and willingness to use engagement tools to engage in policy formulation through e-participation. United Nations (2020) also found that the presence of strong network ties among citizens as actors help increase citizens' engagement in giving views for policy formulation.…”
Section: 3mentioning
confidence: 99%
See 2 more Smart Citations
“…erefore, it is important for Chinese enterprises and all other organizations to take action to ensure justice in the recruitment process. For instance, managers could ensure a fair procedure in recruitment and more transparent decision making, in order to reduce the factors, which lead to unfairness [55,56]. e study is not without its limitations.…”
Section: Discussionmentioning
confidence: 99%